The Role of Internal Audit and Internal Control on the Quality of Financial Reports at PT. ABC - Mursyida, Indah; Maulina, Rina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The quality of financial reports is a measure of the extent to which a company's financial reports meet various characteristics and attributes that are considered important. In this research, the author uses a quantitative research approach. It has the systematic nature of field research. The types of data for this research are primary data and secondary data. The main data in this research was taken directly from distributing questionnaires to PT. ABC. The population in this observation is all employees at PT. ABC as many as 125 people. The sample selection technique used in this research was a saturated sample or the entire population was sampled, namely 125 people. However, when distributing the questionnaire to 125 samples, only 120 people received answers, so only 120 samples were used in this research. The research results state that internal audit and internal control have a partial and simultaneous effect on the quality of financial reports.